Perbandingan Tingkat Kebugaran Jasmani Siswa SMA di Kota Bandung Berdasarkan Moda Transportasi Aktif Berjalan Kaki dan Bersepeda ke Sekolah - Farhat Mahmudi; Asep Sumpena; Sufyar Mudjianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to compare the physical fitness levels of high school students in Bandung, Indonesia, based on active commuting modes of walking and cycling to school. A comparative quantitative study with a cross-sectional design was conducted involving 36 students selected through purposive sampling, consisting of 17 cyclists and 19 walkers. Physical fitness was assessed using the high-priority ALPHA-Fitness Test Battery, including body mass index (BMI), waist circumference, handgrip strength, standing long jump, and cardiorespiratory fitness (VO₂max). Data were analyzed using the Shapiro-Wilk test, Levene's test, Independent Sample t-test, and Mann-Whitney U test at a significance level of 0.05. The results showed no significant differences between the cycling and walking groups in BMI (p=0.975), waist circumference (p=0.155), handgrip strength (p=0.210), standing long jump (p=0.303), or VO₂max (p=0.274). Nevertheless, the cycling group consistently demonstrated slightly higher mean values and effect sizes across most fitness indicators. It can be concluded that walking and cycling to school did not result in significant differences in the physical fitness levels of high school students in Bandung, possibly due to the low dose of physical activity and the relatively small sample size. Keywords: Walking, Cycling, Physical Fitness, Adolescents, Active Commuting